2019
DOI: 10.1021/acs.jproteome.9b00370
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipidomics Investigation of the Temporal Dynamics after Ischemic Brain Injury

Abstract: Sphingolipids (SPLs) have been proposed as potential therapeutic targets for strokes, but no reports have ever profiled the changes of the entire range of SPLs after a stroke. This study applied sphingolipidomic methods to investigate the temporal and individual changes in the sphingolipidome including the effect of atorvastatin after ischemic brain injury. We conducted sphingolipidomic profiling of mouse brain tissue by liquid chromatography–electrospray ionization tandem mass spectrometry at 3 h and 24 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
4
24
0
3
Order By: Relevance
“…Our finding of increased circulating plasma levels of longchain ceramides, in our case specifically C18:0-ceramide, is in keeping with previously published preclinical and clinical studies [12,14]. Murine studies showed that plasma levels of long-chain ceramides even though rising in the first hours of AIS reached their peaks at least 24 h after ischemic insult [12] with similar findings in the ischemic tissue [11,29,30]. Our study is the first report to date which now recapitulates these animal findings in humans.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of increased circulating plasma levels of longchain ceramides, in our case specifically C18:0-ceramide, is in keeping with previously published preclinical and clinical studies [12,14]. Murine studies showed that plasma levels of long-chain ceramides even though rising in the first hours of AIS reached their peaks at least 24 h after ischemic insult [12] with similar findings in the ischemic tissue [11,29,30]. Our study is the first report to date which now recapitulates these animal findings in humans.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to the rising long-chain ceramide levels, we observed decreasing over time levels of very-long-chain ceramides which is also consistent with reported results [12,13]. Production of long-chain and very-long-chain ceramides is regulated by different ceramide synthases [35]; in contrast to long-chain ceramides, very-long-chain ceramides have been linked to cell proliferation and potentially neuroprotective effects during anoxia [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In that respect, various T H cell populations and T REG cells in the ischemic hemisphere have been found to amass on the first day after MCAO [ 53 , 54 , 55 ]. Moreover, it can be argued that neurons are an important source of S1P [ 56 ], suggesting that as cerebral blood flow (CBF) decreases and neuronal damage worsens, the release of S1P into the ischemic core could contribute to the maintained high S1P levels [ 40 , 57 ]. This, in turn, would establish a new S1P gradient allowing various immune cell populations to invade the peri-infarct cortex.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that there were several ceramides in common in the LAA cerebrovascular disease and age-related CSVD when they were compared with control, probably due to enrollment of patients with acute stroke. Studies have found several ceramides were increased after stroke [36,37]. However, there were no statistically significant differences in the proportion of patients with acute stroke between the LAA cerebrovascular disease and age-related CSVD groups.…”
Section: Comparison Of Sphingolipids Between Laa Cerebrovascular Disementioning
confidence: 97%